Analisis Sistem Operasional pada PT. Temas Suzue Indonesia - Mulyo, Adiguna (UNIVERSITAS KALBIS, 2025)
An operational system is a system that is used to simplify and speed up operational processes that occur by recording everything in the system and storing it in a database. That way the data will always be recorded, stored properly, will not be lost and can be used anytime when needed. This research was conducted to develop an operational system that already exists but is not optimal in use, because the process of creating documents manually will be very difficult when creating and storing them, this system should be able to automate the process. Interview and observation methods were used by researchers to collect the data needed to conduct this research. This research produces a proposed system that can be applied to maximize system performance to assist and be useful in operational processes.